2006
DOI: 10.1016/j.ijar.2005.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Learning probabilistic decision graphs

Abstract: Probabilistic decision graphs (PDGs) are a representation language for probability distributions based on binary decision diagrams. PDGs can encode (context-specific) independence relations that cannot be captured in a Bayesian network structure, and can sometimes provide computationally more efficient representations than Bayesian networks. In this paper we present an algorithm for learning PDGs from data. First experiments show that the algorithm is capable of learning optimal PDG representations in some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…We will also study the problem of inducing CG-PDGs from data, that so fas has been successfully addressed for discrete PDGs [17,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will also study the problem of inducing CG-PDGs from data, that so fas has been successfully addressed for discrete PDGs [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In our example, this simply CG-PDG model and subsequently simplifying the obtained CG-PDG model by merging nodes in the structure. We will review the structural operation of merging nodes used in [17] which is defined only for nodes representing discrete random variables.…”
Section: Examplementioning
confidence: 99%
“…Previous comparative studies have demonstrated the strength of the PDG model as a secondary structure in probability estimation . In the study of Jaeger et al (2004), a PDG is learned from a Junction Tree model and thereafter a series of merging operations is applied. These operations effectively remove redundant parameters and parameters with little or no data-support.…”
Section: Learning the Pdg Classifiermentioning
confidence: 99%
“…Probabilistic decision graphs (PDGs) constitute a class of probabilistic graphical models that naturally capture certain context specific independencies (Boutilier et al, 1996) that are not easily represented by other graphical models (Jaeger, 2004;Jaeger et al, 2006). This means that the PDG model can capture some distributions with fewer parameters than classical models, which in some situations leads to a model less prone to over-fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been work by Lowd and Domingos (2008) which learns a Bayes net while directly penalizing the complexity of the associated arithmetic circuit. Another approach for representing probability distributions which particularly takes benefit of context specific independence is based on Probabilistic Decision Graphs (PDG) (Jaeger et al 2006). However, similar to BN, PDG are not guaranteed to be efficient in the most general cases.…”
Section: Related Workmentioning
confidence: 99%